Study on co-crystal formation of ibuprofen and oxalic acid via slow cooling technique / Fatin Nabilah Abdollah - Abdollah, Fatin Nabilah (2017)
Pharmaceutical co-crystals can improve the solubility, physicochemical properties as well as their chemical properties. In this study, the interaction between Active Pharmaceutical Ingredients (API) Ibuprofen (IBP) and oxalic acid (OXA) to crystallize into a newly formed drug is experimented viz slow cooling method with the cooling rate of 0.5°C/min by decreasing the temperature from 60°C to 20°C. The mol ratio of IBP:OXA ranging from 1:0.5 to 1:4.5 in both solvents, ethanol and propanol. However, co-crystal formation is limited to 1:2.5 to 1:4.5 in ethanol and 1:1.5 to 1:4.5 in propanol. IBP-OXA co-crystals are then analysed using optical microscopy, Fourier Transform Infrared Spectroscopy (FTIR), Powder X-Ray Diffractometer (PXRD) and Differential Spectrometer Calorimetry (DSC). Morphology obtained are long rod-shaped crystals. The PXRD analysis shows that the co-crystals produced are in impure state. The IR spectra and thermal analysis using FTIR and DSC proves the existence of co-crystals. This indicates that the cocrystallization of Ibuprofen and Oxalic Acid can be conducted by using slow cooling method to increase its bioavailability in the pharmaceutical industry.